ANTI-MYCOBACTERIAL ACTIVITY OF CAPPARIS SPINOSA L. EXTRACT AGAINST CLINICAL ISOLATES OF MYCOBACTERIUM TUBERCULOSIS - Ehsanifar, Azadeh; Kazemipoor, Nadia; Fouladi, Bahman (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objective: Tuberculosis (TB) has been one of the biggest global health issues for decades. Emerging forms of the disease; however, after many years since the discovery of the last effective treatment for this disease, the emerging forms of it have made scientists worried about the disease. Most herbs have anti-microbial properties; however, there was no research on the impact of fruit Capparis spinosa on TB. This study was conducted to evaluate the anti-microbial effects of bacterial C. spinosa. Methods: In this study, methanolic extract at maximum efficiency to maintain existing substances was prepared by the freeze dryer device and to determine the minimum inhibitory concentration of bacteria's growth. The proportional method was used on 7 clinical samples and one reference sample H37RV with its six concentrations (80-50-25-10-1-0/2 mg/ml). In addition, to determine the effects of plant extracts in combination with rifampin, all samples were tested by the supplement combination or cover combination of these two materials. All tests were performed twice. The methanol extract of the plant at the concentration of 25 mg/mL in all samples has inhibitory effect on the growth. Results: In study, clinical samples with a lethal dose of RIFAMPIN, it was shown that none of the samples have drug resistance. The results have revealed that the methanol extract has an anti-mycobacterial effect. Conclusion: The results of this study indicate that Capparis spinosa possess considerable anti-mycobacterial properties in the laboratory. These results can be used as a background for further future studies on this species.